SISTEM PENILAIAN KARYA SENI RUPA DAN KERAJINAN - Suharto - (FBS UNY, 2009)
This writing is aimed to give wider concept to society or readers especially for candidates of fine art teacher to make assessment for fine art works. It is indeed such a standard, but a candidate of assessor must be able to make and have an objective assessment. The results show that assessing fine arts both pure fine art and applied ones can be viewed from some point other than fine art structure viewing only idea in the form of message, imagination, illusion, desire, and fantasy of the artist other than considering work physical form element, principle, media and effective technique. There are some ways to assess a work from aesthetical side resulted in the writing. Firstly, the presence of initial reaction (clarifying initial identification) of an art work. Secondly, exposition involving further identification of art elements in an art work, which the art elements including : line, plane, color, value, format, texture, and space. Another, there are design principles consisting of balance, harmony, central, interest, movement, proportion, restriction, model pattern, rhythm, unity, and variety. Beside considering fine art elements, it also requires to consider design elements including : balance, emphasis, euryhmy, harmony, horror vacui, limitation, movement, pattern proportion, rhythm, unity, and variety. Elements and principles are much higher to consider the design and closer with its pure art consideration of using fine art component consisting of theme or subject matter, form, and meaning or content. Thirdly, analyzing by further identification on order of organization in an art work as art principles used to arrange art elements in an art work. Fourthly, interpretation of meaning as a communication form the artist to feel the atmosphere and idea in the art work by considering the history, creative process, environment, political/social condition, innovation, philosophy, and economy. Fifthly, evaluation process to consider the intended interpretation both on meaning and artistic service in the art work. The benefit expected from the research is giving the public wider insight to know more on the assessment of fine art works that the common society and academician know qualified art work objectively and subjectively. Kata kunci: penilaian, karya seni, dan proses evaluasi